At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To find the equation of the tangent line to the graph of [tex]\( f(x) = -\frac{1}{3} x^3 \)[/tex] at [tex]\( x = -1 \)[/tex], follow these steps:
1. Calculate the derivative of [tex]\( f(x) \)[/tex] to find the slope of the tangent line:
The function is [tex]\( f(x) = -\frac{1}{3} x^3 \)[/tex].
The derivative [tex]\( f'(x) \)[/tex] is found using the power rule [tex]\( \frac{d}{dx} x^n = n x^{n-1} \)[/tex].
[tex]\[ f'(x) = -\frac{1}{3} \cdot 3 x^2 = -x^2 \][/tex]
2. Evaluate the derivative at [tex]\( x = -1 \)[/tex] to get the slope of the tangent line:
[tex]\[ f'(-1) = -(-1)^2 = -1 \][/tex]
So, the slope of the tangent line at [tex]\( x = -1 \)[/tex] is [tex]\( -1 \)[/tex].
3. Find the function value at [tex]\( x = -1 \)[/tex] to get the point of tangency:
[tex]\[ f(-1) = -\frac{1}{3} (-1)^3 = -\frac{1}{3} \cdot (-1) = \frac{1}{3} \][/tex]
Thus, the point of tangency is [tex]\( (-1, \frac{1}{3}) \)[/tex].
4. Use the point-slope form of the equation of a line to find the equation of the tangent line:
The point-slope form is [tex]\( y - y_1 = m(x - x_1) \)[/tex], where [tex]\( m \)[/tex] is the slope and [tex]\((x_1, y_1)\)[/tex] is the point of tangency.
Plugging in the values [tex]\( m = -1 \)[/tex], [tex]\( x_1 = -1 \)[/tex], and [tex]\( y_1 = \frac{1}{3} \)[/tex]:
[tex]\[ y - \frac{1}{3} = -1 (x - (-1)) \][/tex]
Simplifying, we get:
[tex]\[ y - \frac{1}{3} = -1 (x + 1) \][/tex]
[tex]\[ y - \frac{1}{3} = -x - 1 \][/tex]
[tex]\[ y = -x - 1 + \frac{1}{3} \][/tex]
[tex]\[ y = -x - \frac{3}{3} + \frac{1}{3} \][/tex]
[tex]\[ y = -x - \frac{2}{3} \][/tex]
So, the equation of the tangent line in slope-intercept form is:
[tex]\[ y = -x - \frac{2}{3} \][/tex]
1. Calculate the derivative of [tex]\( f(x) \)[/tex] to find the slope of the tangent line:
The function is [tex]\( f(x) = -\frac{1}{3} x^3 \)[/tex].
The derivative [tex]\( f'(x) \)[/tex] is found using the power rule [tex]\( \frac{d}{dx} x^n = n x^{n-1} \)[/tex].
[tex]\[ f'(x) = -\frac{1}{3} \cdot 3 x^2 = -x^2 \][/tex]
2. Evaluate the derivative at [tex]\( x = -1 \)[/tex] to get the slope of the tangent line:
[tex]\[ f'(-1) = -(-1)^2 = -1 \][/tex]
So, the slope of the tangent line at [tex]\( x = -1 \)[/tex] is [tex]\( -1 \)[/tex].
3. Find the function value at [tex]\( x = -1 \)[/tex] to get the point of tangency:
[tex]\[ f(-1) = -\frac{1}{3} (-1)^3 = -\frac{1}{3} \cdot (-1) = \frac{1}{3} \][/tex]
Thus, the point of tangency is [tex]\( (-1, \frac{1}{3}) \)[/tex].
4. Use the point-slope form of the equation of a line to find the equation of the tangent line:
The point-slope form is [tex]\( y - y_1 = m(x - x_1) \)[/tex], where [tex]\( m \)[/tex] is the slope and [tex]\((x_1, y_1)\)[/tex] is the point of tangency.
Plugging in the values [tex]\( m = -1 \)[/tex], [tex]\( x_1 = -1 \)[/tex], and [tex]\( y_1 = \frac{1}{3} \)[/tex]:
[tex]\[ y - \frac{1}{3} = -1 (x - (-1)) \][/tex]
Simplifying, we get:
[tex]\[ y - \frac{1}{3} = -1 (x + 1) \][/tex]
[tex]\[ y - \frac{1}{3} = -x - 1 \][/tex]
[tex]\[ y = -x - 1 + \frac{1}{3} \][/tex]
[tex]\[ y = -x - \frac{3}{3} + \frac{1}{3} \][/tex]
[tex]\[ y = -x - \frac{2}{3} \][/tex]
So, the equation of the tangent line in slope-intercept form is:
[tex]\[ y = -x - \frac{2}{3} \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.